2011
DOI: 10.1007/s13313-011-0046-x
|View full text |Cite
|
Sign up to set email alerts
|

Chemical approaches to manage coffee leaf rust in drip irrigated trees

Abstract: The purpose of this study was to assess the efficiency of chemical approaches to manage coffee leaf rust (CLR) in drip-irrigated coffee trees. Coffea arabica plants of the Catuaí Vermelho IAC 144 cultivar were subjected to applications of protective and systemic fungicides . Foliar application of the systemic fungicide epoxiconazol was performed at predefined dates (calendar) and after ascertaining that CLR was present in 10% of plants. A fungicide + systemic insecticide (cyproconazol + thiamethoxam) was appli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 11 publications
2
20
0
1
Order By: Relevance
“…As to the use of calcium and potassium silicates, results showed that application was not efficient either as foliar spray or to the soil (Carré-Missio et al 2009Lopes et al 2013). On the other hand, treatment with Viçosa mixture and Bordeaux mixture have reduced rust incidence by 75 % due to the effect of copper sulfate (Souza et al 2011;Carvalho et al 2012).…”
Section: Alternative Control Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…As to the use of calcium and potassium silicates, results showed that application was not efficient either as foliar spray or to the soil (Carré-Missio et al 2009Lopes et al 2013). On the other hand, treatment with Viçosa mixture and Bordeaux mixture have reduced rust incidence by 75 % due to the effect of copper sulfate (Souza et al 2011;Carvalho et al 2012).…”
Section: Alternative Control Methodsmentioning
confidence: 99%
“…Among systemic fungicides, triazoles are applied alone or in mixtures with QoI (strobilurin) fungicides, and are applied either on the leaves or in the soil (in this case, together with systemic insecticides for control of leaf miner). The combined use of copper-based fungicides with systemic fungicides has the additional advantage of providing copper to the plants, besides reducing the risk of selecting fungicideresistant rust populations (Souza et al 2011). Various rules can be used to aid the decision of when to start fungicide applications.…”
Section: Chemical-based Control Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Rust control in Brazil is routinely performed with the use of systemic fungicides sprayed on the leaves (two applications) or applied to soil (one application), and/or copper fungicide (4 to 5 foliar applications) Souza et al, 2011). Due to increasing concern regarding the environment and health of the consumers, the search for high quality coffee without pesticide residues has been a constant demand (Rodrigues, 2007).…”
Section: Rust Caused By the Fungus Hemileia Vastatrixmentioning
confidence: 99%
“…The disease causes early leaf fall, resulting in a die-back of productive branches and fruits. Consequently, in the following year, the plants have a low fruit load (Souza et al, 2011). The most important strategy for the control of the coffee leaf rust is the use of resistant varieties.…”
Section: Introductionmentioning
confidence: 99%